2007
DOI: 10.2337/dc07-0275
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Adipokine Retinol-Binding Protein-4 in Relation to Renal Function

Abstract: OBJECTIVE -Retinol-binding protein (RBP)-4 was recently identified as an adipokine that induces insulin resistance. In the current study, we investigated RBP-4 serum levels in diabetic and nondiabetic patients on chronic hemodialysis (CD) compared with control subjects with a glomerular filtration rate Ͼ50 ml/min. The majority of the diabetic subjects used oral hypoglycemic agents or insulin.RESEARCH DESIGN AND METHODS -RBP-4 was determined by enzyme-linked immunosorbent assay in control subjects (n ϭ 59) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 25 publications
6
46
3
Order By: Relevance
“…Increased circulating RBP4 levels in T2D subjects could be the result of decreased renal clearance of RBP4 caused by different levels of renal insufficiency in these subjects (78)(79)(80). These studies are supported by the fact that patients with end-stage kidney failure have significantly higher circulating RBP4 levels than healthy controls and that serum creatinine levels independently predict RBP4 concentrations in both controls and patients with kidney failure (81). There is an ongoing debate on the possible influence of transthyretin on circulating RBP4 levels via RBP4's decreased renal clearance (24,25).…”
Section: Rbp4 In Childhood/adolescent Obesity and Insulin Resistancesupporting
confidence: 71%
“…Increased circulating RBP4 levels in T2D subjects could be the result of decreased renal clearance of RBP4 caused by different levels of renal insufficiency in these subjects (78)(79)(80). These studies are supported by the fact that patients with end-stage kidney failure have significantly higher circulating RBP4 levels than healthy controls and that serum creatinine levels independently predict RBP4 concentrations in both controls and patients with kidney failure (81). There is an ongoing debate on the possible influence of transthyretin on circulating RBP4 levels via RBP4's decreased renal clearance (24,25).…”
Section: Rbp4 In Childhood/adolescent Obesity and Insulin Resistancesupporting
confidence: 71%
“…There was a possibility that the discrepancy of the findings from those of previous reports may result from the analysis using different assay kit of RBP4. Ziegelmeier et al [24] reported a fourfold increase in serum RBP4 levels in patients with chronic hemodialysis compared with control subjects. Their patients included both diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum RBP4 concentrations have been observed in patients of type 2 DM with nephropathy [15] and in subjects on chronic hemodialysis [16]. Serum creatinine can independently predict RBP4 concentrations even in control subjects with a GFR >50 mL/min [16].…”
Section: Common Carotid Ultrasoundmentioning
confidence: 99%